2018
DOI: 10.1155/2018/2952386
|View full text |Cite
|
Sign up to set email alerts
|

The Extracellular Environment of the CNS: Influence on Plasticity, Sprouting, and Axonal Regeneration after Spinal Cord Injury

Abstract: The extracellular environment of the central nervous system (CNS) becomes highly structured and organized as the nervous system matures. The extracellular space of the CNS along with its subdomains plays a crucial role in the function and stability of the CNS. In this review, we have focused on two components of the neuronal extracellular environment, which are important in regulating CNS plasticity including the extracellular matrix (ECM) and myelin. The ECM consists of chondroitin sulfate proteoglycans (CSPG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 197 publications
1
59
0
Order By: Relevance
“…In previous studies, CSPGs were highly expressed in the site of spinal cord injury. 54,55 In the present study, we found that the fluorescence intensity of CS56 has been decreased after the supplementation of pure ChABC into the spinal cord section. In addition, the fluorescence intensity of CS56 of the spinal cord section was also decreased by the culture medium of PEI-SPIONs/ChABC/ SCs.…”
Section: Discussionsupporting
confidence: 60%
“…In previous studies, CSPGs were highly expressed in the site of spinal cord injury. 54,55 In the present study, we found that the fluorescence intensity of CS56 has been decreased after the supplementation of pure ChABC into the spinal cord section. In addition, the fluorescence intensity of CS56 of the spinal cord section was also decreased by the culture medium of PEI-SPIONs/ChABC/ SCs.…”
Section: Discussionsupporting
confidence: 60%
“…Among these key inhibitory molecules, CSPGs are the most prominent. CSPGs, a proteoglycan family characterized by chondroitin sulfate side chains, are thought to be released predominantly from neurons and scar-forming astrocytes (Quraishe et al, 2018). It has long been thought that CSPGs are crucial inhibitory factors of CNS axonal regeneration, making them a primary cause of the inhibitory roles of the glial scar (McKeon et al, 1991).…”
Section: Chondroitin Sulfate Proteoglycansmentioning
confidence: 99%
“…Perineuronal nets around neurons regulate neuritic growth and synaptogenesis during early life. Maturation of these extracellular matrices restricts synaptic plasticity and stabilizes functional synapses (Bikbaev et al, 2015;Clarris et al, 2000;Lensjø et al, 2017;Quraishe et al, 2018;Sorg et al, 2016;Valenzuela et al, 2014;van 't Spijker & Kwok, 2017) and disrupting them can extend early sensitive periods (e.g., monocular deprivation in the cerebral cortex or thalamus; Lensjø et al, 2017) and allow synaptic potentiation of normally plasticityresistant neurons (Carstens, Phillip, Pozzo-Miller, Weinberg, & Dudek, 2016). Substantial regional differences in the expression of extracellular matrix proteins during development have been reported (Dauth et al, 2016;Sonntag, Blosa, Schmidt, Rübsamen, & Morawski, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These mesh-like extracellular structures envelop neuronal processes and regulate the number and types of synapses. Their maturation is associated with the end of early critical periods of synaptogenesis in several brain regions (Bikbaev, Frischknecht, & Heine, 2015;Clarris, Uwe Rauch, & Key, 2000;Lensjø, Lepperød, Dick, Hafting, & Fyhn, 2017;Quraishe, Forbes, & Andrews, 2018;Sorg et al, 2016;Valenzuela et al, 2014;van 't Spijker & Kwok, 2017). Finally, the rapid changes associated with growth in the structure necessitate substantial energy: a small study addressed this issue by examining age-related changes in vasculature.…”
Section: Introductionmentioning
confidence: 99%